The Influence Of Financial Behavior On Investment Decisions With Financial Literacy As A Mediation Variable: Case Study In PKN STAN Learning Assignment Students - Dinarjito, Agung (Politeknik Keuangan Negara STAN, 2023)
Making investment decisions is very important for investors because it will affect profits or losses. Various factors have influenced investment decisions, one of which is financial behavior. Study assignment students are employees who get the opportunity to continue their study. Because they already earn income, it is important to see the students' understanding regarding decision making. This study aims to see the influence of the financial behavior of study assignment students at the STAN State Finance Polytechnic in making decisions with financial literacy as an intervening variable. The financial behavior measured is overconfidence, herding, loss aversion, and risk perception. The result is only the financial literacy variable, risk perception, has a significant effect on investment decisions. Regarding the financial literacy variable, it is evident that only the overconfidence and risk perception variables influence it. Regarding the existence of financial literacy as an intervening variable, it is proven only by overconfidence and risk perception which are able to provide an indirect relationship to investment decisions. Financial literacy has succeeded in fully mediating the relationship of overconfidence to investment decisions and for risk perception only as partially mediation.